Community perceptions of corruption by public officials - Voce, Alexandra (Trends & issues in crime and criminal justice, 2024)
In July 2023 the National Anti-Corruption Commission (NACC) commenced operation. Prior to this, we surveyed a large sample of online Australians (n=11,304) about their perceptions of corruption and legitimacy among public officials. A sizeable minority of respondents believed that over half of all politicians and government institutions were involved in corruption. Younger, unemployed and First Nations respondents perceived higher levels of corruption, as did respondents with lower levels of education and those living in socio-economically disadvantaged areas. Perceptions of corruption were associated with diminished levels of perceived legitimacy of public officials, but this relationship was moderated by other factors. Perceived corruption and the legitimacy of public officials go hand in hand. Implementing measures to address one may help improve the other.